A feasibility study on Philippine Business High School - Cagape, Adonis R.; Rodriguez, Federico Jose S.; Santiago, Jennifer Marie R.
Everyone has the right to education. Each individual has the right to learn about various fields of study and apply them to their everyday life. One must realize the importance of the field of business in its social and economic growth. Businesses not only provide employment but also contribute to the economy. Suggestions, like the introduction of a Bachelor of Science in Entrepreneurship in the college sector, are being voiced in order to formally educate the Filipinos on the do's and don'ts in the business arena. Knowing that business is a possible key to the country's development economically and socially, Philippine Business High School (PBHS) was thought of. PBHS is a non-profit, non-stock educational institution offering business courses incorporated in formal secondary education for Filipinos. This feasibility study was conducted to explore the details and overall effect of the school's establishment in five aspects (namely, market, technical, organizational, financial and social profitability) as it is introduced to the Philippine setting. The planning horizon used is five years. The market study discussed whether the establishment of PBHS is plausible in the Philippines through various analyses on demand, supply, competitors and marketing strategies to be used. After which, the type of organization was constructed and the technical aspect of the school was explored as well. Areas discussed in the technical study included site selection, procedure on needed permits to operate, facility layout, and the school curriculum (both basic and special business curricula) and policies. Next was the discussion of the financial aspect of PBHS. Evaluation of costs and possible sources of funds were the main concerns of this section. And lastly, the social profitability of PBHS was determined through a quantitative analysis of the benefits and costs of the school to the Philippine society. The construction and operation of PBHS was concluded to be feasible in all five aspects of the study. There was a substantial demand for a business oriented secondary school having the target market as Filipino high school students interested in business, living in the Quezon City area. Simple yet effective marketing strategies were used to reach out to the consumers of the services and at the same time stay within the set marketing budget. All construction and operation planning and the corresponding costs were met through analyzing all gathered information acquired in research and interviews with different personalities. And finally, a school definitely benefits the society as long as its establishment and operation is cost effective and of good quality.